PENGEMBANGAN EKONOMI LOKAL KABUPATEN/KOTA PROVINSI DAERAH ISTIMEWA YOGYAKARTA MENGGUNAKAN TIPOLOGI KLASEN DAN LOCATION QUOTIENT - Rudy Badrudin (Jurnal Riset Manajemen dan Bisnis, 2012)
This research analyzed local economic development strategy in 4 regencies and 1 city in Province of DIY based on the data of year 2001 to 2008. The method used to analyze the hypotheses were Klassen Typology and Location Quotient. Using hypothesis test for means and ANOVA, the results showed that each regency and city in same diagram area with Klassen Typology have spesific local economic development strategyto develop region.Keywords: klassen typology, location quotient